Effects of rumensin and bovatec on growth, feed intake, and feed efficiency in dairy calves - J. A. Isch; Michael V. Scheffel; Evan C. Titgemeyer; E. C. Thomas (Kansas Agricultural Experiment Station Research Reports, 1999)
One hundred Holstein heifers were used to examine the effects of monensin (Rumensin®) and lasalocid (Bovatec®) included in calf starter and grower diets. Heifers were assigned alternately at birth to a starter feed containing either Rumensin (28 g/ton, 90% dry matter basis) or Bovatec (40 g/ton, 90% dry matter basis). The Bovatec group was switched to a starter feed containing 28 g Bovatec/ton (90% dry matter basis) at 6 weeks of age. Both groups were switched at 8 weeks of age to grower diets designed to deliver 100 mg/head/day of either Rumensin or Bovatec. No treatment differences were observed between birth and 8 weeks of age. Heifers were moved from individual hutches at 8 weeks of age to group pens (five heifers/pen) and remained on the same treatment for the next 84 days. During this 84-day period, heifers receiving Rumensin gained more weight at a faster rate and tended to be more efficient than heifers fed Bovatec. No differences were observed in feed intake, skeletal growth as measured by hip height, or body condition score.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Calves; Replacement heifers; Rumensin; Bovatec